2018
DOI: 10.1016/j.mex.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method for the transduction of primary pediatric glioma neurospheres

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…The neurosphere stem cell culture is generally accepted as the gold standard for primary glioma stem cells [ 34 , 35 ]. Recently, two studies have employed a reliable protocol for lentiviral cell transduction of primary DIPG cell lines cultured as neurospheres, by exposing the cells to FBS for a short period of time [ 36 , 37 ]. They have demonstrated that the short-term exposure of the cells to serum and a rapid return to serum-free conditions, improve the neurosphere transduction efficiency without inducing a change in their stem cell proprieties.…”
Section: Discussionmentioning
confidence: 99%
“…The neurosphere stem cell culture is generally accepted as the gold standard for primary glioma stem cells [ 34 , 35 ]. Recently, two studies have employed a reliable protocol for lentiviral cell transduction of primary DIPG cell lines cultured as neurospheres, by exposing the cells to FBS for a short period of time [ 36 , 37 ]. They have demonstrated that the short-term exposure of the cells to serum and a rapid return to serum-free conditions, improve the neurosphere transduction efficiency without inducing a change in their stem cell proprieties.…”
Section: Discussionmentioning
confidence: 99%
“…VUMC-HGG-05 [16] (giant-cell GBM), VUMC-HGG-09 (IDH1 R132H) and VUMC-HGG-14 are resection-derived glioblastomas. VUMC-HGG-11 [17] is a thalamic midline glioma harbouring a H3.3 K27M mutation. All models are FANCD2 wildtype as confirmed by whole-genome sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured as neurospheres as previously described [15,17,18]. Cells were only used when confirmed mycoplasm negative and short-tandem repeat (STR) analysis was performed to ensure cell line identities.…”
Section: Methodsmentioning
confidence: 99%
“…For the pediatric cells, there was an Institutional Review Board-approved protocol M-1608 from the Hospital Sant Joan de Deu Barcelona. Primary pediatric DIPG cells (HSJD-DIPG-007) were derived from autopsy of a 6-year-old female and were transferred as neurospheres, exponentially growing in suspension in tumorsphere media (TSM) supplemented with corresponding growth factors (15,16), and checked for mycoplasma contamination.…”
Section: Brain Tumor Specimenmentioning
confidence: 99%